Efficacy of myo‐inositol and d‐chiro‐inositol combination on menstrual cycle regulation and improving insulin resistance in young women with polycystic ovary syndrome: A randomized open‐label study. Issue 2 (10th November 2021) - Kachhawa, Garima; Senthil Kumar, Krithika V.; Kulshrestha, Vidushi; Khadgawat, Rajesh; Mahey, Reeta; Bhatla, Neerja
Abstract: Objective: To compare the effect of myo‐inositol and d ‐chiro‐inositol in combination (MI + DCI) with combined hormonal contraceptive (CHC) on menstrual cycle regulation in young Indian women with polycystic ovary syndrome (PCOS). Methods: Seventy young women with PCOS aged 15–24 years with delayed cycles were randomized into two groups and were treated for 6 months with MI + DCI (550 + 150 mg, 3.6:1 ratio) twice a day and CHC (ethinyl estradiol 20 µg + drospirenone 3 mg) once a day. Results: Spontaneous menses resumed in 28 (84.85%) young women on MI + DCI, compared with withdrawal bleeding in 34 (100%) on CHC. The mean cycle length reduced with both MI + DCI (124.54 ± 8.08 to 57.75 ± 3.00 days, P < 0.001) and CHC (105.88 ± 7.96 to 30.53 ± 2.95 days, P < 0.001). Regular menstrual cycles were established in 9 (27.27%) young women with MI + DCI ( P = 0.001) and 30 (88.23%) with CHC ( P < 0.001). Three months after stopping the treatment, 24 young women (85.71%) on MI + DCI and 25 (73.53%) on CHC continued to have spontaneous cycles. Anti‐Müllerian hormone decreased with both the drugs ( P = 0.001), whereas luteinizing hormone ( P = 0.001) and testosterone ( P = 0.04) decreased with CHC and homeostatic model assessment of insulin resistance ( P < 0.001) with MI + DCI. Conclusion: Myo‐inositol and d ‐chiro‐inositol in combination (3.6:1 ratio) are effective in regularizing menstrual cycles and improving insulin resistance. Trial registration: Clinical Trials Registry of India (CTRI/2018/03/012643). http://ctri.nic.in/Clinicaltrials/pmaindet2.php?trialid=20969&EncHid=&userName=myo‐inositol Abstract : Myo‐inositol and d ‐chiro‐inositol combination, as a non‐hormonal option, is effective in regularizing menstrual cycles and improving insulin resistance in young Indian women with polycystic ovary syndrome.